1993
DOI: 10.1029/93jb02383
|View full text |Cite
|
Sign up to set email alerts
|

In situ high P‐T X ray diffraction studies on three polymorphs (α, β, γ) of Mg2SiO4

Abstract: Unit cell volumes of the beta ([•) and spinel (7) phases (Mg2SiO4) have been measured under simultaneous high pressure and high temperature using synchrotron X ray radiation, in a cubic anvil apparatus. With volume-temperature data at constant pressure, we determine the average volume thermal expansion coefficients of the [• phase from 724 to 872 K at 7.6 GPa to be 2.28(_0.45)x10-5/K and of the 7 phase from 759 to 962 K at 9.8 GPa to be 1.71(_0.14)x10-5/K. Thermodynamic relations are used to constrain the temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
47
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(54 citation statements)
references
References 38 publications
6
47
1
Order By: Relevance
“…To avoid transforming wadsleyite to the olivine phase, the measurements were conducted only at temperatures up to 600øC (873 K) where the transformation is inhibited by kinetics. As suggested in a previous study using powder or polycrystalline samples, back transformation from wadsleyite to olivine occurs at 7 GPa and 973 K [Meng et al, 1993]. In Figure 3 we compare the X-ray diffraction spectra for our wadsleyite sample at ambient conditions, at 8 GPa and room temperature, and at the peak P-T conditions of 7.3 GPa and 873 K. It is clear that within the detectability of the current experiment, the wadsleyite phase was preserved up to the peak pressure and temperature conditions of the current study (Figure 2).…”
Section: 2supporting
confidence: 60%
See 1 more Smart Citation
“…To avoid transforming wadsleyite to the olivine phase, the measurements were conducted only at temperatures up to 600øC (873 K) where the transformation is inhibited by kinetics. As suggested in a previous study using powder or polycrystalline samples, back transformation from wadsleyite to olivine occurs at 7 GPa and 973 K [Meng et al, 1993]. In Figure 3 we compare the X-ray diffraction spectra for our wadsleyite sample at ambient conditions, at 8 GPa and room temperature, and at the peak P-T conditions of 7.3 GPa and 873 K. It is clear that within the detectability of the current experiment, the wadsleyite phase was preserved up to the peak pressure and temperature conditions of the current study (Figure 2).…”
Section: 2supporting
confidence: 60%
“…Recently, elasticity measurements have been extended up to transition zone pressures at room temperature using ultrasonic techniques in the multianvil apparatus (P > 12 GPa [Li et al, 1996a]) and Brillouin spectroscopy in the diamond anvil cell (DAC) [Zha et al, 1998;Sinogeikin et al, 1998]. To date, the elastic properties of wadsleyite at high temperatures have only been estimated from equation of state studies using X-ray diffraction techniques [Meng et al, 1993;Fei et al, 1992;Hazen et al, 1990]. No information about the temperature derivative of the shear modulus for wadsleyite has been published, except the brief report by Li et al [1998b].…”
Section: Introductionmentioning
confidence: 99%
“…The cell bulk modulus indicates a linear trend with H content. (Meng et al, 1993) for all samples. We then estimated the bulk modulus for the anhydrous sample at 1200 ºC to be about 156 GPa, and at 600 ºC to be about 170 GPa.…”
Section: Relative Effects Of Hydration Versus Temperaturementioning
confidence: 99%
“…Deviatoric stresses can be determined from the diffraction of a standard material pressurised within the cell, and recent studies have shown that it can be characterised quite readily. In high-P/T experiments under constant ram load competing factors which influence the measured pressure include the deviatoric stress (which saturates at some 3 GPa), the thermal pressure due to the thermal expansion of the sample (which will act to increase P) and mechanical weakening of the anvils and cell materials on increasing T (which reduces the effective P) [17,18].…”
Section: "Large Volume" High-p/t Apparatusmentioning
confidence: 99%
“…On the other hand, mineralogical studies formed only a minority of the early work done at the Photon Factory. Many [17,19] of them have been single-stage experiments on the phase relations of the olivine-wadsleyite-ringwoodite phases of the (Mg,Fe)2SiO4 system; perovskite phases such as CaSiO3 [18], neighborite [20], and (Mg,Fe)SiO3 [21][22][23][24][25] have also been investigated using both single-stage and two-stage arrangements. In the latter, one or more of the second-stage cubic anvils is constructed from sintered diamond to allow the transmission of the diffracted beam.…”
Section: "Large Volume" High-p/t Apparatusmentioning
confidence: 99%